Power-aware node-disjoint multipath source routing with low overhead in MANET. (17th December 2009) - Bheemalingaiah, M.; Naidu, M.M.; Rao, D. Sreenivasa; Varaprasad, G.
With the advance of wireless communication technologies, small-size and high-performance computing and communication devices like laptops and personal digital assistants are increasingly used in daily life. After the success of second generation mobile system, more interest was started in wireless communications. This interest had led to two types of the wireless networks such as infrastructure wireless network and infrastructure less wireless network, also called mobile ad hoc network (MANET). The research challenges in MANET are related to the routing, security, reliability, scalability, quality of services, internetworking, power consumption and multimedia applications. All the mobile nodes of MANET operate on the battery power; hence power consumption becomes an important issue in MANET. It proposes a power-aware node-disjoint multipath source routing (PNDMSR) for real-time traffic, which balances the node energy utilisation to increase the network lifetime. It takes the network congestion into account to reduce the routing delay across the network, and increases the reliability of the data packets reaching the destination.